Study on Novel Materials for Nitrogen and Phosphorus Removal from Aqueous Phase - Xu, Zhihua; Zhang, Daofang; Wu, Lingling (Asian Journal of Chemistry, 2013)
The study on novel adsorption materials has significant practical value for the removal of nitrogen and phosphorus from eutrophicated natural water bodies. In this research, a novel material was developed by using cement, zeolite, sludge and peat, which showed high mechanical strength and excellent adsorption capacity under optimum conditions. Batch experiments and biological aerated filter were employed to evaluate the efficiency of removal of nitrogen and phosphorus. The batch experimental results showed that the adsorption capacity of this novel material was affected by temperature and reaction time. Long term run of biological aerated filter showed that when stable biological film was formed, 30 % of ammonia (NH4+), 28 % of total nitrogen (TN), 55 % of total phosphorus (TP) and 60 % of chemical oxygen demand (COD) in the feed water were removed and the effluent met the requirement of water quality standard for landscape water from recycling of city effluent in China (GB18921-2002).